PENDIDIKAN ISLAM DALAM KONSEPSI LEMBAGA DAN AJARAN - Moh Asvin Abdurrohman (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
Islamic boarding school education today can be classified into three forms. First, Islamic boarding schools, whose education and teaching methods use the sorogan or dam method, namely a kyai, teach students based on classical books written in Arabic by medieval scholars with a translation system. Generally, this kind of Islamic Boarding School is